Used infant mattresses and sudden infant death syndrome in Scotland: case-control study. Issue 7371 (2nd November 2002) - Tappin, David; Brooke, Hazel; Ecob, Russell; Gibson, Angus
Abstract: Objective: To examine the proposition that a used infant mattress is associated with an increased risk of sudden infant death syndrome. Design: Case-control study. Setting: Scotland (population 5.1 million, with about 53 000 births a year). Participants: 131 infants who died of sudden infant death syndrome between 1 January 1996 and 31 May 2000 and 278 age, season, and obstetric unit matched control infants. Main outcome measures: Routine use of an infant mattress previously used by another child and place of last sleep. Results: Routine use of an infant mattress previously used by another child was significantly associated with an increased risk of sudden infant death syndrome (multivariate odds ratio 3.07, 95% confidence interval 1.51 to 6.22). Use of a used infant mattress for last sleep was also associated with increased risk (6.10, 2.31 to 16.12). The association was significantly stronger if the mattress was from another home (4.78, 2.08 to 11.0) than if it was from the same home (1.64, 0.64 to 4.2). Conclusion: A valid significant association exists between use of a used infant mattress and an increased risk of sudden infant death syndrome, particularly if the mattress is from another home. Insufficient evidence is available to judge whether this relation is cause and effect.